Samoocena, a wybrane elementy pozycji społecznej judoków = Self-assessment and selected elements of the social position of judokas - Patrycja Janowska; Marta Wojdat; Magdalena Antkowiak; Robert Stępniak; Marek Adam (Kazimierz Wielki University, 2016)
Janowska Patrycja, Wojdat Marta, Antkowiak Magdalena, Stępniak Robert, Adam Marek. Samoocena, a wybrane elementy pozycji społecznej judoków = Self-assessment and selected elements of the social position of judokas. Journal of Education, Health and Sport. 2016;6(9):664-673. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.158969 http://ojs.ukw.edu.pl/index.php/johs/article/view/3890         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016.       Samoocena, a wybrane elementy pozycji społecznej judoków Self-assessment and selected elements of the social position of judokas   Janowska Patrycja1, Wojdat Marta1, Antkowiak Magdalena1, Stępniak Robert2, Adam Marek3   1Studenckie Koło Naukowe "WyKoNa", Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska 2Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska 3Zakład Sportów Walki, Akademia Wychowania Fizycznego i Sportu, Gdańsk, Polska   Corresponding author: Stępniak Robert Ph. D Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego, ul. Sportowa 2, 85-091 Bydgoszcz Polska email: <robi1969@wp.pl>     Słowa kluczowe: samoocena, pozycja społeczna, zawodnicy judo Keywords: self-esteem social position, judo fighters     Samoocena, a wybrane elementy pozycji społecznej judoków Self-assessment and selected elements of the social position of judokas   Streszczenie   Cel: Określenie liczbowe poziomu samooceny populacji judoków, oraz znalezienie ewentualnych związków z czynnikami określającymi pozycje społeczną. Materiał i metody: Przebadano 53 osobowa grupę judoków i byłych -nadal trenujących judoków używając ankiety samooceny Rosenberga SES, w polskiej adaptacji. Wyniki: Podgrupa społeczna judoków wykazuje się wysoką samooceną, wysokim wykształceniem i ponadprzeciętnym wynagrodzeniem za prace zarobkową. Wnioski: Istnieją istotne związki pomiędzy wynikami samooceny SES, a czynnikami określającymi daną osobę w społeczeństwie.         Abstract   Aim: To determine the numerical level of self-esteem of the judokas population and to find possible links with the factors determining the social position. Material and Methods: 53 current and formerly judokas - still trained. Research conducted using the self-assessment surveys Rosenberg SES in Polish adaptation. Results: Subgroup social judokas showed high self-esteem, high education and above-average remuneration paid for the work. Conclusions: There are significant relationships between the results of self-assessment - SES, and the factors defining a person in society.